Association between enjoyment, physical activity, and physical literacy among college students: a mediation analysis - Yan, Wenjing; Chen, Leqin; Wang, Lina; Meng, Yihan; Zhang, Ting; Li, Hongjuan (Frontiers in Public Health, 2023)
Background Physical literacy and enjoyment are important factors that affect physical activity. Purpose This work studies whether physical activity enjoyment (PAE) mediates the association between moderate to vigorous physical activity (MVPA) and physical literacy (PL) among college students. Methods Chinese college students were recruited using the Perceived Physical Literacy Instrument Scale (PPLI-SC), the International Physical Activity Questionnaire Short Form (IPAQ-SF), and the Physical Activity Enjoyment Scale. The SPSS Hayes process macro (model 4) was used to analyze the direct impact and the indirect impact. Pearson correlation, independent sample t-tests, and linear regression were used to analyze the relationship between indicators. Results The study surveyed 587 boys and 1,393 girls with a total of 1,980 valid questionnaires. MVPA, PAE, and PL of boys were significantly higher than girls (p < 0.01). The correlation analysis showed that MVPA, PL, and PAE were significantly correlated (p < 0.01). The results showed the direct effect of PL on MVPA was still statistically significant (β = 0.067, p < 0.05) after adding PAE variables; PAE has a positive effect on MVPA after controlling PL (β = 0.170, p < 0. 01). PL has a positive effect on PAE (β = 0.750, p < 0.01). PL impacted MVPA as explained by a 65.58% mediating effect of enjoyment. Conclusion Physical activity enjoyment mediates the relationship between PL and MVPA among college students. This means that even high PL among student may not imply that they are physically active if they do not enjoy physical activity.